Global, Regional and Local Perspectives on the Economies of Southeastern Europe Proceedings of the 14th International Conference on the Economies of the Balkan and Eastern European Countries (EBEEC) in Florence, Italy, 2022 - Persiani, Niccolò; Vannini, Ilaria Elisa; Giusti, Martina; Karasavvoglou, Anastasios; Polychronidou, Persefoni (Springer Proceedings in Business and Economics, 2023)
XIII, 357 p. 79 illus., 68 illus. in color.